Moderating effect of financial literacy on the relationship between socioeconomic status and depression. (2nd January 2023) - Ishii, Ryo; Ohyama, Takuya; Endo, Hideki
Abstract: This study examined the moderating effect of financial literacy on the relationship between socioeconomic status and depression. A questionnaire survey of 2173 employees using multiple regression and simple slope analyses showed that the relationship between socioeconomic status and depression was weaker among Japanese employees with high financial literacy than among those with low financial literacy. Interpretation from a financial capability framework perspective, including a sense of control and the potential for prevention and intervention of socioeconomic status-related depression through educational interventions related to financial literacy, was discussed.